g - 6 = 2

To find the value of the unknown variable we need to isolate the variable g,

g - 6 = 2

g - 6 + 6 = 2 + 6

**g = 8 Answer.**

You can now input this value in the above equation to verify the answer, therefore

g - 6 = 2

8 - 6 = 2

2 = 2

LHS = RHS

Proved.

QUESTION:-

g-6=2

SOLUTION:-

In this problem, we have to simplify in order to get the value of g or till the simplification is possible.

g - 6 = 2

Now add 6 to both sides in order to cancel -6 on LHS (Left Hand Side)

g - 6 = 2

g - 6 + 6 =2 + 6

g = 8

Hence Simplified!

g-6=2

g-6=2

g=8

because we want to try to get the variable by itself, we add 6 to both sides

g - 6 = 2

To find the value of " g " , we have to try to get " g " alone . In order to get " g " alone , we should first add 6 on both sides .

By adding 6 on both sides , you should get :

g = 8 which is your answer for " g "